Combined analysis of charm-quark fragmentation-fraction measurements - Lisovyi, Mykhailo; Verbytskyi, Andrii; Zenaiev, Oleksandr (The European physical journal. C, Particles and fields, 2016)
A summary of measurements of the fragmentation of charm quarks into a specific hadron is given. Measurements performed in photoproduction and deep inelastic scattering in $$e^{± }p$$e±p, pp and $$e^+e^-$$e+e-collisions are compared, using up-to-date branching ratios. Within uncertainties, all measurements agree, supporting the hypothesis that fragmentation is independent of the specific production process. Averages of the fragmentation fractions over all measurements are presented. The average has significantly reduced uncertainties compared to individual measurements.
Gesehen am 28.05.2020